The Effect of Handling Facilities and Methods on Quality of The Fish by Fisherman on Purse Seine Board, In Gamhoku - Kour, Femsy; Akerina, Febrina Olivia (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Generally each type of fish has different pattern of deterioration. Quality deterioration and high postharvest damage was caused by fishing method, poor handling process, the length of supply chain, poor handling facilities. This research was aimed to know about handling facilities on Purse seine board and its handling method; and to analyze fish quality using pH and organoleptic. The first step in this research was to observe the handling on the board then measure the pH of fish using pH metes. And also there was 30 panelist who did sensory test using organoleptic instrument on the board. The result showed that the handling facilities on board were coolbox, ice and hold, it showed that their apply good handling facilities. The average value of pH between 6,10 – 6,27, where the highest score was Ikan Selar (Selar crumenopthalmus) and the lowest score was Ikan Layang (Decapterus macarellus). The result of organoleptic was between 8,62-8,91, it showed that the tested fishes were fresh.